The Influence of Early Mobilization on the Healing Process in Post-Section Patients in Hospitals - Nofa Anggraini; Dea Veronica; Resita Sri Pamela; Rismalia; Septiany Herman S (Postgraduate, University of Mataram, 2025)
Cesarean section (Sectio Caesarea) is a medical procedure that often results in postoperative wounds requiring optimal management to support recovery. Early mobilization plays a critical role in accelerating the wound healing process by improving blood circulation and enhancing tissue regeneration. This study aimed to analyze the influence of early mobilization on the healing process in post-cesarean section patients in several hospitals. This quantitative study used a descriptive correlational design with a cross-sectional approach. Data were collected through questionnaires assessing early mobilization practices and direct observation of wound healing indicators. The study involved 40 postpartum mothers who underwent cesarean sections, selected through purposive sampling from four hospitals—Cilincing Hospital, RSIA Bunda Jakarta, RS Mekar Sari Bekasi, and RSU Ibu Pusat Jakarta—during December 2024. Data analysis included univariate (frequency distribution) and bivariate tests using the Chi-Square method. The statistical test showed a significant relationship between early mobilization and wound healing, with a p-value of 0.007 (< 0.05), indicating that early mobilization positively influences postoperative recovery. Patients who engaged in early mobilization exhibited faster wound healing compared to those who delayed movement. In conclusion, early mobilization is proven to be an effective intervention in enhancing the healing process among post-cesarean section patients. The findings highlight the importance of implementing early mobilization protocols as part of standard postoperative nursing care to improve maternal health outcomes.